The correlation between body mass index and the type of foot arches with the risk of hallux valgus in children aged 13–14 years old - Vittala, Govinda; Sundari, Luh Putu Ratna; Bhakti Krisnanda, I Putu Radhe; Semariasih, Ni Komang Dewi (International Journal of Research in Medical Sciences, 2021)
Background: Hallux valgus is a deformity characterized by a change in the shape of the thumb with symptoms of swelling, redness and pain. Hallux valgus is progressive where there is a lump at the base of the thumb which can occur due to the weakness of the muscles and ligaments around the first metatarsophalangeal joint. The purpose of this study was to determine the relationship between body mass index and the type of foot arches on the risk of hallux valgus in children aged 13–14 years. Methods: This research is a cross sectional analytic study with simple random sampling technique. The number of samples are 99 children (39 males, 60 females) aged 13–14 years. The variables measured were body mass index using body weight scales and a stature meter, the type of foot arches using a wet footprint test, and hallux valgus with a goniometer. Results: Our study shows that there is no significant correlation between body mass index and hallux valgus at the level of 0.157. However, there is a significant correlation between the type of foot arches and hallux valgus at the 0.003 level. In addition, there is a significant correlation between body mass index and foot arches. Conclusions: There was a significant relationship between body mass index and foot arches and foot arches with the risk of hallux valgus. However, body mass index is not directly related to hallux valgus condition.